Call for a Paradigm Shift in the Genetic Management of Fragmented Populations - Ralls, Katherine; Ballou, Jonathan D.; Dudash, Michele R.; Eldridge, Mark D. B.; Fenster, Charles B.; Lacy, Robert C.; Sunnucks, Paul; Frankham, Richard (Conservation letters, 2018)
Thousands of small populations are at increased risk of extinction because genetics and evolutionary biology are not well‐integrated into conservation planning–a major lost opportunity for effective actions. We propose that if the risk of outbreeding depression is low, the default should be to evaluate restoration of gene flow to small inbred populations of diploid outbreeding organisms that were isolated by human activities within the last 500 years, rather than inaction. We outline the elements of a scientific‐based genetic management policy for fragmented populations of plants and animals, and discuss the reasons why the current default policy is, inappropriately, inaction.